Leader versus manager: Lessons from top business executives - Chow, Tong Wooi (goodwood publishing, 2020)
Purpose: This article discusses the key differences between leadership and management. It also examines the business organizational executive’s leadership styles of seven selected top executives: Donald Trump, Steve Jobs, Bill Gates, Mark Zuckerberg, Jeff Bezos, Jack Ma, and Tony Fernandez. Research methodology: The methodological approach of the study focuses on the review of published literature postulating on the differences in the characteristics and functions of leadership and management. Results: Findings from the literature review indicate evidence that shows the differences and similarities between these two concepts of leaders and managers or leadership and management. The study also reveals that these top business executives demonstrated the contemporary leadership paradigms of transformational, charismatic, and servant leadership. Limitations: One limitation is the review approach of the paper. The other is the analysis of leadership styles based on those top executives from the business sector. Contributions: The article provides insights into the understanding of the evolvement of organizational management and the preferred leadership styles of top business executives. The findings on the leadership styles of the top business leaders add to the significance of the study.